Programmable Shape-Shifting Micelles - Chien, Miao-Ping; Rush, Anthony M; Thompson, Matthew P; Gianneschi, Nathan C (Angewandte Chemie (International ed.), 2010)
Getting in shape: DNA‐brush copolymer amphiphiles assemble into micelles with morphologies determined by selective interactions that allow manipulation of the magnitude of steric and electrostatic repulsions in the micelle shells. Cylinder‐to‐sphere phase transitions occur when an input DNA sequence is added to the micelles (see picture).